2020
DOI: 10.1186/s13059-019-1908-8
|View full text |Cite|
|
Sign up to set email alerts
|

Host-associated microbiomes are predicted by immune system complexity and climate

Abstract: Background: Host-associated microbiomes, the microorganisms occurring inside and on host surfaces, influence evolutionary, immunological, and ecological processes. Interactions between host and microbiome affect metabolism and contribute to host adaptation to changing environments. Meta-analyses of hostassociated bacterial communities have the potential to elucidate global-scale patterns of microbial community structure and function. It is possible that host surface-associated (external) microbiomes respond mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 155 publications
1
83
1
2
Order By: Relevance
“…Some of the taxa detected in our study may be part of the microbiome essential for an effective immune response and survival, but it is di cult to discern which taxa this would be without differential mortality between larval cohorts. There is a correlation between host microbiome diversity and the complexity of the immune system, with more stable microbiomes in invertebrates with innate immune systems [48]. It is worth identifying this stable, core microbiome in ecologically and commercially important taxa as a means to better understand mechanisms of environmental response and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the taxa detected in our study may be part of the microbiome essential for an effective immune response and survival, but it is di cult to discern which taxa this would be without differential mortality between larval cohorts. There is a correlation between host microbiome diversity and the complexity of the immune system, with more stable microbiomes in invertebrates with innate immune systems [48]. It is worth identifying this stable, core microbiome in ecologically and commercially important taxa as a means to better understand mechanisms of environmental response and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial communities associated with the skin (i.e., skin or cutaneous microbiome) play a significant role in pathogen defense and may, therefore be involved in predisposition to different diseases and contribute to host fitness 6 8 . Due to its direct exposure to the environment, the skin microbiome is thought to be much more dynamic than the microbiome of other parts of the animal such as the gut 9 , 10 , and consequently, the role of the environment is expected to be strong in shaping its composition, diversity and function 11 , 12 . Moreover, host-specific factors such pH, sebum production, temperature and moisture are known to shape the skin microbiome and its defensive function 7 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Host associated factors are less studied but clearly also play a role because multiple studies have demonstrated that the skin microbiomes of co-occurring species are significantly different 18 , 29 , 36 , 37 . Only few general patterns have been identified for host-associated factors, whereas global-scale patterns in microbial diversity have been tied to environmental factors such as bioclimate and habitat 10 , 19 . Amphibians depend on microbial environmental reservoirs, such as forest soil, to maintain diverse skin microbiomes 30 , 38 and the peculiar conditions of the amphibian skin selects for particular microbial taxa to be integrated in the skin-associated communities 37 , 39 .…”
Section: Introductionmentioning
confidence: 99%
“…The turtle shell microbiome may simultaneously serve as an indicator of both turtle health and overall ecosystem status. Very generally, the external microbiomes of organisms are influenced by climatic effects, rather than "top-down" or species-specific effects [2]. This suggests that turtles could be susceptible to pathogenic microbial growth on external surfaces, including for novel reptile-associated [3] and known human pathogens [4] present in the environment.…”
Section: Introductionmentioning
confidence: 99%